2001
DOI: 10.1002/ijc.10186
|View full text |Cite
|
Sign up to set email alerts
|

Lipopeptide‐based melanoma cancer vaccine induced a strong MART‐27‐35‐cytotoxic T lymphocyte response in a preclinal study

Abstract: Key words: melanoma; cancer; vaccine; lipopeptides; CD8 ϩ T cell responses; peptides; immunotherapyCytotoxic T lymphocytes play a central role in the anti-tumor immune response by recognizing small antigenic peptides bound to major histocompatibility complex (MHC) class-I molecules on cancer cells. Identification of tumor antigens and their optimal antigenic peptides over the past decade opened new approaches to the understanding of melanoma antigenicity and allowed development of peptide-based vaccine strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The elucidation of cellular and molecular mechanisms by which lipopeptides interact with the adaptive immune system could led to significant improvement of lipopeptide‐based vaccines currently being developed for human pathogens and cancers 1, 10, 12. In the present study, we found that totally synthetic lipopeptides induced up‐regulation of a number of DC surface markers, including MHC class I, MHC class II, CD80 and CD86 molecules, and showed that the nature of the lipid moiety is a crucial factor in the effect of lipopeptide Ag on DC.…”
Section: Discussionmentioning
confidence: 99%
“…The elucidation of cellular and molecular mechanisms by which lipopeptides interact with the adaptive immune system could led to significant improvement of lipopeptide‐based vaccines currently being developed for human pathogens and cancers 1, 10, 12. In the present study, we found that totally synthetic lipopeptides induced up‐regulation of a number of DC surface markers, including MHC class I, MHC class II, CD80 and CD86 molecules, and showed that the nature of the lipid moiety is a crucial factor in the effect of lipopeptide Ag on DC.…”
Section: Discussionmentioning
confidence: 99%
“…As an additional consideration, immunogens with increased immunogenicity can be easily obtained by fusing peptides to cytokines utilizing recombinant DNA technology, by conjugating peptides to larger molecules, particularly if the carrier proteins contain strong T‐helper epitopes, and by direct peptide polymerization with glutaraldehyde and other chemical processes (4–6). These encouraging perspectives explain the high interest and commitment of investigators to the goal of developing effective anti‐cancer peptide vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…The TAP‐deficient cell line T2, the myeloid cell line K562 and the mouse melanoma cell line B16F10 were purchased from American Type Culture Collection (ATCC). B16AAD (B16F10 cells expressing a chimeric major histocompatibility complex class I molecule consisting of the α1 and α2 domains of HLA‐A2 and the α3 domain of H‐2D d ) was a kind gift from Professor Gahéry‐Ségard H 35 . All the above cell lines were maintained in RPMI‐1640 medium (Invitrogen, Grandland, NY, USA.)…”
Section: Methodsmentioning
confidence: 99%